Ferroelectric tunnel junctions: promise, achievements and challenges - Park, Sung Hyuk; Lee, Hyeon Ji; Park, Min Hyuk; Kim, Jihyun; Jang, Ho Won (Journal of physics. D, Applied physics, 2024)
Ferroelectric tunnel junctions (FTJs) have been the subject of ongoing research interest due to its fast operation based on the spontaneous polarization direction of ultrathin ferroelectrics and its simple two-terminal structure. Due to the advantages of FTJs, such as non-destructive readout, fast operation speed, low energy consumption, and high-density integration, they have recently been considered a promising candidate for non-volatile next-generation memory. These characteristics are essential to meet the increasing demand for high-performance memory in modern computing systems. In this review, we explore the basic principles and structures of FTJs and clarify the elements necessary for the successful fabrication and operation of FTJs. Then, we focus on the recent progress in perovskite oxide, fluorite, 2-dimensional van der Waals, and polymer-based FTJs and discuss ferroelectric materials expected to be available for FTJs use in the future. We highlight various functional device applications, including non-volatile memories, crossbar arrays, and synapses, utilizing the advantageous properties of ferroelectrics. Lastly, we address the challenges that FTJ devices currently face and propose a direction for moving forward.